Public Perception of Massage Therapy - Özlem Özdinç (Selcuk University, 2020)
Massage therapy, as a service, is susceptible to churn for its misconceived efficiency and practice. However, therapists and massage businesses could frame messages that highlight, for instance, their service proficiency or price promotions on the public's perception of massage to overcome such misconception. We tested this prediction in two studies. In study 1 (n = 1,925), we distinguished four groups of individuals by their massage perception (positive, negative) and whether they had ever received a massage (yes, no). In study 2 (n = 1,209), we observed the four types of people that study 1 determined to compare the influences of a service expert and discount on their perceptions of massage therapy in a 2 (therapist: expert, nonexpert) x 2 (discount: yes, no) Solomon four-group experiment. There is evidence that positive perception is prone to service expert among those who had received a massage before. Those who experienced massage service for the first time, however, were prone to a bargain. Despite their lack of practical experience, these results imply that inexperienced and emerging therapists (e.g., students on practicum, interns) could help a massage business create customers when their imperfect services are bundled with an economic incentive. An expert therapist could, then, convert the initially discount-prone receivers of massage into quality-prone repeating customers and justify a price premium.